WOMEN REPRESENTATION AND WILDE'S IDEOLOGY AS SEEN IN OSCAR WILDE'S A WOMAN OF NO IMPORTANCE: - - Sri Saraswati; Emilia Tetty Harjani (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2022)
The study talked about women representation and Wilde’s ideology regarding women as portrayed in Wilde’s A Woman of No Importance. The study was carried out using gender approach and specifically employed existentialist feminism and genetic structuralism theories. The results showed that there were three types of women represented in the play including a new woman, a rebellious woman, and an independent woman. Meanwhile, based on the discussion, regarding the human facts and his world view depicted in the play, Oscar Wilde’s ideology was equality. Keywords: women representation, ideology, existentialist feminism, genetic structuralism, equality